New Insights on Bone Tissue and Structural Muscle-Bone Unit in Constitutional Thinness - Bailly, Mélina; Boscaro, Audrey; Thomas, Thierry; Féasson, Léonard; Costes, Frédéric; Pereira, Bruno; Hager, Jorg; Estour, Bruno; Galusca, Bogdan; Metz, Lore; Courteix, Daniel; Thivel, David; et al. (Frontiers in Physiology, 2022)
Graphical Abstract